Estudo da resistência a flexão de compósitos poliméricos compostos por fibras curtas de bambu e resíduo de cobre - WANZELER, Vitória Beatriz da Silva (2022)
Industry opts for sustainable and low-cost paths. Therefore, in this present work, composites were developed incorporating untreated 30mm bamboo fibers (FB30mmNT) and treated with 5% NaOH (FB30mmTR) and Copper Residue (RCU) varying in 10%, 20% and 30%. The FB were treated for 2h, the RCU with a granulometry of 100mesh. Flexion tests followed the ASTM D790 standard. Flexural strength reached a value of 95.98MPa for FB30mmNT/RCU and 121.64MPa for FB30mmTR/RCU.